2007
DOI: 10.7205/milmed.172.6.676
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Testosterone in the Treatment of Chronic Postvasectomy Pain Syndrome: Case Report and Review of the Literature

Abstract: The purpose of this article is to describe a simple, intellectually reasonable, initial treatment for all subacute and chronic postvasectomy scrotal pains. The use of intramuscular testosterone cypionate in a dose of 400 mg monthly for 3 months is described for patients suffering from painful sperm granuloma at the vasectomy site or in the epididymis, circumventing the need for other medical or surgical approaches. Excellent results have been achieved in patients and a representative case is illustrated. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…From animal studies, there is a general consensus that the penetration of germ cells into the epididymis or the space of the vas deferens will produce autoimmune and/or inflammatory reactions, which will lead to the formation of a sperm granuloma [ 28 ]. These opalescent granulomatous nodules appear at the end of the vas deferens or epididymis and consist of a central part of degenerated sperm, which is surrounded by a layer of epithelioid macrophages and, in turn, by loose connective tissue rich in lymphocytes and plasma cells [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…From animal studies, there is a general consensus that the penetration of germ cells into the epididymis or the space of the vas deferens will produce autoimmune and/or inflammatory reactions, which will lead to the formation of a sperm granuloma [ 28 ]. These opalescent granulomatous nodules appear at the end of the vas deferens or epididymis and consist of a central part of degenerated sperm, which is surrounded by a layer of epithelioid macrophages and, in turn, by loose connective tissue rich in lymphocytes and plasma cells [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Despite the several studies conducted after different periods from gonadectomy (a few days, 3-4 months) (9,21,(25)(26)(27) and the studies on the effects R. Ahmadi, Sh. Oryan of sex steroids on pain modulation through the different kinds of painful stimulation (8,28,29) there are still conflicting data and complexity (7,30) in this area particularly from a time-dependent aspect of issue.…”
Section: Introductionmentioning
confidence: 98%
“…In experiments with electrical stimulation to induce tail withdrawal in rats, it has been observed that castration resulted in significant reduction of pain threshold which returned to normal level on substitution with testosterone therapy (9). Recently the effects of testosterone in the treatment of chronic postvasectomy pain syndrome (10) and the protective role of testosterone in the development of temporomandibular joint pain (11) have been established.…”
Section: Introductionmentioning
confidence: 98%